2019
DOI: 10.3390/v11050450
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Epstein-Barr Virus Lytic Reactivation by the Atypical Antipsychotic Drug Clozapine

Abstract: Epstein–Barr virus (EBV), a member of the Herpesviridae family, maintains a lifelong latent infection in human B cells. Switching from the latent to the lytic phase of its lifecycle allows the virus to replicate and spread. The viral lytic cycle is induced in infected cultured cells by drugs such as sodium butyrate and azacytidine. Lytic reactivation can be inhibited by natural products and pharmaceuticals. The anticonvulsant drugs valproic acid and valpromide inhibit EBV in Burkitt lymphoma cells. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…On the other hand, several psychoactive agents, including clozapine, have antiviral effects [ 57 ]. Clozapine inhibited the reactivation of the Epstein–Barr virus lytic cycle in induced Burkitt lymphoma cells and some clozapine metabolites were found to suppress the replication of dengue virus, respiratory syncytial virus, rotavirus, and human immunodeficiency virus [ 58 ].…”
Section: Clinical Questionsmentioning
confidence: 99%
“…On the other hand, several psychoactive agents, including clozapine, have antiviral effects [ 57 ]. Clozapine inhibited the reactivation of the Epstein–Barr virus lytic cycle in induced Burkitt lymphoma cells and some clozapine metabolites were found to suppress the replication of dengue virus, respiratory syncytial virus, rotavirus, and human immunodeficiency virus [ 58 ].…”
Section: Clinical Questionsmentioning
confidence: 99%
“…Epstein–Barr virus (EBV) maintains a lifelong latent presence in human B cells and switching from the latent to the lytic cycle in infected cultured cells allows EBV to replicate and spread. Clozapine was found to inhibit reactivation of the EBV lytic cycle by decreasing the levels of the viral lytic genes BZLF1, BRLF1, and BMLF1 [ 18 ]. Thioridazine, another antipsychotic drug, was confirmed to inhibit the cell entry of EBOV by directly interacting with the glycoprotein of EBOV.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies demonstrated that VPA inhibits the reactivation of Epstein-Barr virus (EBV) lytic cycle in vitro due to VPA's HDAC inhibitory activity. However, despite the fact that VPD does not have this HDAC inhibitory property, it still inhibits reactivation of the EBV lytic cycle [70,71]. Furthermore, a recent study has shown that VPA could also have a potential antiviral effect against RNA virus SARS-CoV-2, as it reduces the number of angiotensin-converting enzyme 2 (ACE-2) in endothelial cells, the main cellular receptor that this coronavirus uses to enter the cell [72].…”
Section: Antiviral Mechanism Of Vpa and Related Derivativesmentioning
confidence: 99%